Alcohol and Drug Use Screening among Justice-Involved Persons. Issue 1 (2nd January 2022) - Bradshaw, Spencer D.; Wang, Eugene W.; Meeks, Samuel; Chroback, Kelly; Hirsch, Sarah; Goad, Chloe
ABSTRACT: (a) Objective: This study examined the reliability and validity of the Texas Risk Assessment System (TRAS) alcohol and drug use screeners. (b) Method: We examined internal consistency, inter-item correlations, and used confirmatory factor analysis (CFA), and item response theory (IRT) to assess item-specific information regarding a single latent dimension of substance use severity. (c) Results: Results supported the TRAS alcohol and drug screeners to measure a single dimension of alcohol and drug use severity. More specifically, the instruments appear to be effective screeners of moderate to severe alcohol use problems, and thus effective screeners for referral for further assessment and possible treatment. (d) Conclusions: Treatment can only be provided for problems that are well defined and diagnosed. Continuing evaluation of substance abuse screeners and assessment is important, especially for justice-involved persons. Effective screeners can lead to more people getting needed assessment and treatment. Recommendations were to drop one item on each screener due to redundancy.